PENGARUH ADITIF PADA SINTESIS NANOPARTIKEL Mn2O3 MELALUI PROSES SOL-GEL - Ningsih, Sherly Kasuma Warda (Jurnal Sainstek, 2013)
Preparation of manganese oxide by sol-gel process has been studied. Mangese nitrate and isopropanol were used as precursor and solvent, respectively. The addition of various additives that used in this research were diethanolamine (DEA), ethylene diamine and ethylene gycol. The powders were formed by drying in the temperature of 110-110 oC and after heating at 500 oC for (1) one hour. The products were obtained black powders. The products were characterized by X-ray diffraction (XRD) and Scanning Electron Microscopy (SEM). The XRD patterns showed Mn2O3 forms were produced generally. Crystallite sizes of Mn2O3 were obtained in the range 54-82 nm. SEM micrograph clearly showed that powder had a bulk surface and hollow with hollow size is 0.1-1.9 m approximately.